Crop wild relatives of Kazakhstani Tien Shan: Flora, vegetation, resources - Sitpayeva, Gulnara T. (Plant Divers, 2019)
This paper presents the results of the field study on species composition, geographical distribution, phytocoenotic diversity and resources of crop wild relatives (CWR) in Kazakhstan's ranges of the Tien Shan Mountains. Taxa of not only cultivated genera of crops are taken into account, but also a wider range of species of high socio-economic importance, including medicinal, fodder, essential oil and other species. List of CWR includes 289 species belonging to 39 families and 145 genera. Among them, 9 species listed in the Red Data book of Kazakhstan: Pistacia vera, Rheum wittrockii, Armeniaca vulgaris, Malus sieversii, Allium pskemense, Allochrusa gypsophilloides, Sorbus sibirica, Vitis vinifera and Artemisia cina. The highest plant diversity is recorded in intermountain plains and river valleys where meadow vegetation forms a high abundance of forage and resource plants. The diversity of wild fruit plants is concentrated in gallery forests. CWR of cereals are confined to dry steppe slopes in low piedmont belt. The populations of almond, pistachio, plum and cherry were recorded at dry slopes of low mountain belt. The estimation of the raw material base for 13 resource plants is given. Only Rumex tianschanicus, Berberis sphaerocarpa are recommended for industrial harvesting; for local pharmacy chain – Mentha longifolia, Origanum vulgare, O. vulgare subsp. gracile, Ziziphora clinopodioides, Hypericum scabrum, Hypericum perforatum, and five Rosa species.